Hesperidin Plays Neuroprotective Effects Against Quinolinic Acid in Human SH-SY5Y Cells: Focusing on ROS Levels and Cell Cycle Arrest - Farzaneh Abbasinezhad-Moud; Emad Azimi; Mehdi Rostami; Elaheh Gheybi; Mohammad Soukhtanloo* (Iranian Society of Pharmacognosy, 2024)
Background and objectives: In some neurodegenerative diseases, an aberrant accumulation of quinolinic acid is frequently associated with the loss of nerve cells and a condition known as neuritis. This is typically caused by an excessive production of free radicals. Studies have shown that hesperidin has potent antioxidant effects, but nothing is known about how it protects against the neurotoxicity induced by quinolinic acid. This study aimed to evaluate the protective effect of hesperidin against quinolinic acid-induced neurotoxicity in the SH-SY5Y neuroblastoma cell line. Methods: The MTT test was used to determine cell viability and protective dosage of hesperidin. Flow cytometry using propidium iodide (PI) staining was used to determine the cell cycle of SH-SY5Y cells after exposure to quinolinic acid in combination with hesperidin. Reactive oxygen species (ROS) levels within cells were also measured using 2', 7'-dichlorodihydrofluorescein diacetate (H2DCFDA) in the mentioned groups. Results: Our results demonstrated that hesperidin had a protective effect against quinolinic acid-induced toxicity at nontoxic concentrations (p<0.001). Moreover, the percentage of apoptotic cells in the sub-G1 phase increased significantly (p<0.001). Hesperidin pretreatment significantly decreased sub-G1 arrest that was induced by quinolinic acid (p<0.001). Hesperidin significantly decreased ROS levels generated by quinolinic acid (p<0.001). Conclusion: The current study showed that hesperidin exerts its effect through antioxidant activity and can be considered a promising neuroprotectant agent against quinolinic acid-induced neurotoxicity in neurodegenerative disorders; however, more research is necessary in this area for the treatment.